How can you extend the product life cycle of a FMCG brand? - Vardar, Nükhet (Henry Stewart Talks, 2017)
Branding in P&G, Marketing of P&G products in Turkey, Stages of the product life cycle (PLC), PLC stages of Orkid, The role of innovation in extending the PLC